Investor Behavior in Venture Capital Investment: An Analytical Study of Georgian and Central-Eastern European Startup Markets - Abuselidze, George; Sarjveladze, Beka (European Journal of Sustainable Development, 2025)
This research paper investigates venture capital investor behaviors within the startup ecosystems of Georgia and Central Europe, providing comparative analysis of these markets. Utilizing a mixed-methods approach, the study integrates qualitative and quantitative data derived from questionnaires distributed to VC investors in both regions. Detailed diagrams visualize critical trends and patterns, enhancing the understanding of investor behavior. The findings reveal distinct investment preferences, regulatory landscapes, and other details in each region. Georgian investors, often navigating an emerging market with limited infrastructure and networks, display cautious investment behavior, prioritizing stable returns and market potential. In contrast, Central-Eastern European investors benefit from more mature ecosystems, demonstrating higher risk tolerance and a greater focus on innovative ventures. Key factors driving investment choices include market potential, innovation levels, startup industry, and regulatory frameworks. The study highlights how these elements interact to influence investor confidence and preferences. For instance, while Central-Eastern European investors are motivated by Innovative Technologies and market size, Georgian investors are more influenced by government incentives and emerging market opportunities. By understanding these behaviors, this paper offers valuable insights for entrepreneurs, policymakers, and investors. It aims to enhance the startup ecosystem in both regions, providing a foundation for more informed and strategic investment decisions. This analysis contributes to the broader discourse on global VC trends, emphasizing the critical role of regional contexts in shaping investor behavior and their implications for emerging markets. Keywords: Venture Capital, Startups, Startup Ecosystem, Georgian Startup market, Investors